India's general elections are a fraud. - Indian Workers' Association (GB); Alliance Against Fascist Dictatorship in India:::Creator::::::::::::
The pamphlet questions the democratic rhetoric represented in the Indian general elections announced for March 1977. The essay argues that the competing party candidates of this election do not provide the people with alternatives to the political, economic, and social programs established by the ruling Congress Party. And if the Indian population were not given diverse range of choices that represent their political interests, the election would only change the face of power but not its established structure and policies.